Analysis of Steel Plate Raw Material Supplier Selection on Rail Using Analytical Hierarchy Process (AHP) and Additive Ratio Assessment (ARAS) Methods at PT. XYZ - Nugroho, Ferdy Akmal; Ernawati, Dira (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
This study aims to select the best steel plate raw material suppliers at PT XYZ using the Analytical Hierarchy Process (AHP) and Additive Ratio Assessment (ARAS) methods. This research involves the process of collecting primary and secondary data which includes identifying criteria for selecting suppliers, collecting data for each criterion, and collecting performance data from suppliers. The results showed that the order of the best supplier of steel plate raw materials at PT XYZ with the largest value, that is, ranked 1st supplier of PT. Steel Kras with a K value of 0.195207, ranked 2nd supplier of PT. Jaraindo with a K value of 0.137696, ranked 3rd supplier of PT. Capris with a K value of 0.135158, ranks 4th supplier of PT. Kamaseta with a K value of 0.116481, ranks 5th supplier of PT. Wima Indo with a K value of 0.106039 and ranked 6th supplier of PT. Cenia Mandiri with a K value of 0.084586. Based on the AHP and ARAS methods, the relative weight of each criterion has been calculated, which helps in evaluating the best or potential suppliers to be selected. In addition, supplier rankings are also determined based on the resulting priority values.